SISTEM PENUNJANG KEPUTUSAN PENGEMBALIAN DANA TABUNGAN ANGGOTA MUTASI DAN PENSIUN MENGGUNAKAN METODE ANALYTICAL HIERARCHICAL PROCESS (AHP) BERBASIS ANDROID - Saputro, Jefry; Faizah, NM; Riyanto, Arif (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2022)
The Jakarta Marine Corps Marine Cooperative Primary (Primkopal Lanmar Jakarta) is a TNI-AL cooperative under the auspices of the Marine Corps which focuses on the savings and loan sector in the South Jakarta City area. The period of work or duty has a period of time, members have savings in the cooperative which must be returned to members when the member has passed away in Jakarta. However, to decide how much members of the cooperative members' savings funds is a big obstacle for this cooperative. So it is necessary to design a Decision Support System (DSS) is a system that can assist someone in making decisions accurately and on target in a more efficient and effective return on cooperative funds. The AHP method in determining eligibility in determining the eligibility of recipients of the Member Savings funds. AHP is used to identify the weight of each criterion taken form the pairwise comparison matrix. The final results in this study are the results of priority returns and savings, which are sorted form those that identify weights and criteria, so that the Primkopal Lanmar Jakarta Cooperative can easily make decisions by looking at these results.